2016 International Conference on Communications (COMM) 2016
DOI: 10.1109/iccomm.2016.7528335
|View full text |Cite
|
Sign up to set email alerts
|

On enhancement of inter-activity for knowledge sharing in eHealth

Abstract: Abstract-Today, knowledge sharing raises as an important issue that challenges for the eHealth management system. It becomes one of the most demanding applications with references to the dynamic inter-activities among different health actors and the complex data structures involved in this application. In this paper, we suggest an activity theory based ontology model to scientifically represent various health actors in the eHealth system. The goal of the suggest model is to enhance the interactivities among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Guo et al (2016) suggested an activity theory grounded on an ontology design to systematically signify numerous health operators in the e-health mechanism. Three typical inter-activities among these health actors were presented.…”
Section: Review Of Selected Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Guo et al (2016) suggested an activity theory grounded on an ontology design to systematically signify numerous health operators in the e-health mechanism. Three typical inter-activities among these health actors were presented.…”
Section: Review Of Selected Articlesmentioning
confidence: 99%
“…They described the theoretical scheme and investigated an instance use case showing how the method can simplify the practice-oriented medical KS over geographical limits. Guo et al (2016) suggested an activity theory grounded on an ontology design to systematically signify numerous health operators in the e-health mechanism. Three typical inter-activities among these health actors were presented.…”
Section: Provided Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…This raises the need to develop the substantial healthcare services with innovative technologies from both industry and academia [3] [4]. A major technical challenge refers to the requirement for the provision of high-quality healthcare services delivered from the Care Provider (CP) like, e.g., a nurse, a doctor, to the Care Receiver (CR) such as a patient [5]. One important research focus associated with this challenge is laid on the problem called appointment scheduling Journal of Service Science and Management [6] [7].…”
Section: Introductionmentioning
confidence: 99%